A study on the determinants of Petroliam Nasional Berhad (PETRONAS) to become employer of choice / Siti Nur Diana Ahmad Kamal - Ahmad Kamal, Siti Nur Diana (2013)
In the modern world, with rapid transformations and new technologies, organizations as the employers need to practice diverse forms of attraction to retain current employees and to attract potential candidates in order to ensure the success and survival of the organization. It is no doubt that the organization is depending on the creativity and performance of the employees because employees are the indicators on achieving goals of the organization. In order to be a good employer, organization must be excellent in providing sources of authority and justice, should be able in offering good pays and extreme employees’ benefits and also portraying the manners and images that are imagined by the society because the organization will be inspirational and endowed with special leadership power that enabled to capture employees to work with them. Thus, it is important for the organization to have the ability to influence people. Employer branding seems to be one of the vital factors to be the employer of choice. The research entitled “A study on the determinants of Petroliam Nasional Berhad (PETRONAS) to become employer of choice” is prepared as the fulfillment of the Bachelor of Business Administration (Hons) Human Resource Management. The purpose of the research is to identify whether the determinants such as employment branding message, expectation of organizational obligation and expectation of employee obligation contributes to being the employer of choice.